Durvalumab With or Without Tremelimumab in Combination With Chemotherapy as First-Line Therapy for Metastatic Non–Small-Cell Lung Cancer: The Phase III POSEIDON Study. Issue 6 (20th February 2023) - Johnson, Melissa L.; Cho, Byoung Chul; Luft, Alexander; Alatorre-Alexander, Jorge; Geater, Sarayut Lucien; Laktionov, Konstantin; Kim, Sang-We; Ursol, Grygorii; Hussein, Maen; Lim, Farah Louise; Yang, Cheng-Ta; Araujo, Luiz Henrique; et al.
Abstract : PURPOSE: The open-label, phase III POSEIDON study evaluated tremelimumab plus durvalumab and chemotherapy (T + D + CT) and durvalumab plus chemotherapy (D + CT) versus chemotherapy alone (CT) in first-line metastatic non–small-cell lung cancer (mNSCLC). METHODS: Patients (n = 1, 013) with EGFR / ALK wild-type mNSCLC were randomly assigned (1:1:1) to tremelimumab 75 mg plus durvalumab 1, 500 mg and platinum-based chemotherapy for up to four 21-day cycles, followed by durvalumab once every 4 weeks until progression and one additional tremelimumab dose; durvalumab plus chemotherapy for up to four 21-day cycles, followed by durvalumab once every 4 weeks until progression; or chemotherapy for up to six 21-day cycles (with or without maintenance pemetrexed; all arms). Primary end points were progression-free survival (PFS) and overall survival (OS) for D + CT versus CT. Key alpha-controlled secondary end points were PFS and OS for T + D + CT versus CT. RESULTS: PFS was significantly improved with D + CT versus CT (hazard ratio [HR], 0.74; 95% CI, 0.62 to 0.89; P = .0009; median, 5.5 v 4.8 months); a trend for improved OS did not reach statistical significance (HR, 0.86; 95% CI, 0.72 to 1.02; P = .0758; median, 13.3 v 11.7 months; 24-month OS, 29.6% v 22.1%). PFS (HR, 0.72; 95% CI, 0.60 to 0.86; P = .0003; median, 6.2 v 4.8 months) and OS (HR, 0.77; 95% CI, 0.65 to 0.92; P = .0030; median, 14.0 v 11.7 months; 24-month OS, 32.9% v 22.1%) were significantly improved with T + D + CT versus CT. Treatment-related adverse events were maximum grade 3/4 in 51.8%, 44.6%, and 44.4% of patients receiving T + D + CT, D + CT, and CT, respectively; 15.5%, 14.1%, and 9.9%, respectively, discontinued treatment because of treatment-related adverse events. CONCLUSION: D + CT significantly improved PFS versus CT. A limited course of tremelimumab added to durvalumab and chemotherapy significantly improved OS and PFS versus CT, without meaningful additional tolerability burden, representing a potential new option in first-line mNSCLC.